1966
DOI: 10.3758/bf03328360
|View full text |Cite|
|
Sign up to set email alerts
|

Some effects of injections of ribonucleic acid

Abstract: Yeast ribonucleic acid (RNA) was first mentioned as having beneficial effects on memory by Cameron and co-workers (1961, 1963) who reported that RNA administered in tablet form or by intravenous injection produced clinical improvement in patients suffering from senile memory impairmenL This effect was later studied by Cook et al (1963) who showed that yeast RNA (160 mg/kg I.P.) increased the rate at which rats learn the response of climbing a pole to escape shock. Recently, however, the suggestion that RNA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1967
1967
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Cook et al (1963) found that injections of yeast RNA caused rats to learn to pole-climb to avoid shock faster than control animals. However, Corson & Enesco (1966), although able to replicate these results with poleclimbing, were unable to obtain increased learning rates using an escape task which required animals to run down an alley to a goal box. Evidently the generality of the results of Cook et al (1963) is limited since they apply to a pole-climbing avoidance response, but not to a running avoidance response.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Cook et al (1963) found that injections of yeast RNA caused rats to learn to pole-climb to avoid shock faster than control animals. However, Corson & Enesco (1966), although able to replicate these results with poleclimbing, were unable to obtain increased learning rates using an escape task which required animals to run down an alley to a goal box. Evidently the generality of the results of Cook et al (1963) is limited since they apply to a pole-climbing avoidance response, but not to a running avoidance response.…”
mentioning
confidence: 83%
“…This is suggested by the relationship between the studies of Cook et al (1963) and Corson & Enesco (1966). There are, of course, many other possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…Recipient groups received the two kinds of RNA extract via intraperitoneal injection. The group injected with the extract from the brains of the conditioned animals showed significantly greater avoidance of the preferred chamber.Recent research has reported beneficial effects on memory due to ribonucleic acid (RNA) administration (Cameron & Solyom, 1961; Cameron et aI, 1963;Cook et al, 1963;Wagner et al, 1966;Corson & Enesco, 1966). There have also been reports of "transfer" effects accomplished through RNA extraction from the brains of trained animals and its injection into naive animals (Babich et aI, 1965;Jacobson et al 1965; Fjerdingstad et al, 1965).…”
mentioning
confidence: 99%
“…Evidence that RNA treatments produce no changes in open field activity has no bearing on this problem. In fact, Corson & Enesco (1966) report RNA to produce changes in instrumental performance that do not arise from the learning process. An additional group of animals trained under RNA but extinguished without RNA would establish the importance of RNA per se on rate of extinction.…”
Section: Comment On Solyom Beaulieu and Enesco By Hugh L Evansmentioning
confidence: 99%
“…Many drugs (amphetamine, caffeine) enhance the tendency to respond but have no effects on learning (e.g., Weiss & Laties, 1962). Crucial information about effects on learning could be gotten by continued testing after RNA injections have ceased.Finally, the extinction data show that animals responding at a high baseline rate generate extinction curves differing slightly from those with a lower Corson & Enesco (1966) report RNA to produce changes in instrumental performance that do not arise from the learning process. An additional group of animals trained under RNA but extinguished without RNA would establish the importance of RNA per se on rate of extinction.…”
mentioning
confidence: 99%